Adverse Drug Reactions in Children - International Surveillance and Evaluation (ADVISE) A Multicentre Cohort Study - Rashed, A.N.; Wong, I.C.K.; Cranswick, N.; Hefele, B.; Tomlin, S.; Jackman, J.; Lee, K.; Hon, K.L.E.; Ong, J.; Ghaleb, M.; Chua, S.S.; Hui, T.M.; et al. (2012)
Background: A previous meta-analysis reported that 9.5 of hospitalized children suffered from an adverse drug reaction (ADR); however, reported incidences among studies varied. Objective: To enhance the knowledge of ADRs in paediatric hospitalized patients at a global level we investigated the incidence and characteristics of ADRs in hospitalized children in European and non-European countries. Methods: A prospective observational cohort study was conducted in academic and non-academic hospitals in five countries: Australia, Germany, Hong Kong, Malaysia and the UK. Children aged 0-18 years admitted during a 3-month period (between 1 October 2008 and 31 December 2009) were recruited. The main outcome measures were incidence, causality and outcome of ADRs. Results: A total of 1278 patients (1340 admissions) were included Australia n=146 (149 admissions), Germany n=376 (407), Hong Kong n=143 (149), Malaysia n=300 (314) and the UK n=313 (321). The median age was 2 years (interquartile range TOR 0-7). Patients received a total of 5367 drugs (median 3; IQR 2-5) and median length of hospital stay was 4 days (IQR 3-7). A total of 380 ADRs were identified in 211 patients. The resultant ADR incidence of 16.5% (95% Cl 14.5, 18.7) varied significantly between countries (p<0.001). The highest incidences were observed in Malaysia and the UK. 65.3% (n=248) of A DRs were found to be probable, and 24% of the ADRs were serious, with one being fatal. Conclusions: By comparing data from five countries in Europe, Asia and Australia we have shown that the incidence of ADRs in hospitalized children is at least as high as incidences published in adults. However, the variation between countries was mainly due to different populations and treatment strategies. Particular attention should be given to opioid use in hospitalized children.